2023
DOI: 10.3389/fmicb.2023.1233178
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus serum RNA transcript isoform composition and proportion in chronic hepatitis B patients by nanopore long-read sequencing

Abstract: IntroductionSerum hepatitis B virus (HBV) RNA is a promising new biomarker to manage and predict clinical outcomes of chronic hepatitis B (CHB) infection. However, the HBV serum transcriptome within encapsidated particles, which is the biomarker analyte measured in serum, remains poorly characterized. This study aimed to evaluate serum HBV RNA transcript composition and proportionality by PCR-cDNA nanopore sequencing of samples from CHB patients having varied HBV genotype (gt, A to F) and HBeAg status.MethodsL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…Previously, serum HBV RNA has been characterized as pregenomic RNA (pgRNA), but more species have been demonstrated in recent years. Serum HBV RNA consists of full-length pgRNA, internally truncated pgRNA, [7][8][9][10][11] 3′ terminally truncated pgRNA, [12][13][14][15] various spliced pgRNA, 10,[13][14][15][16][17][18] subgenomic HBV RNA as well as HBV-human chimeric RNA (Figure 1). (1) Full-length and internally truncated pgRNA: pgRNA was the majority of serum HBV RNA, which was demonstrated through clonal sequencing and Northern blot.…”
Section: Species Of Extracellular/serum Hbv Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, serum HBV RNA has been characterized as pregenomic RNA (pgRNA), but more species have been demonstrated in recent years. Serum HBV RNA consists of full-length pgRNA, internally truncated pgRNA, [7][8][9][10][11] 3′ terminally truncated pgRNA, [12][13][14][15] various spliced pgRNA, 10,[13][14][15][16][17][18] subgenomic HBV RNA as well as HBV-human chimeric RNA (Figure 1). (1) Full-length and internally truncated pgRNA: pgRNA was the majority of serum HBV RNA, which was demonstrated through clonal sequencing and Northern blot.…”
Section: Species Of Extracellular/serum Hbv Rnamentioning
confidence: 99%
“…These discrepancies likely derive from the variations of host factors or HBV genome, as studies reported that the generation of different spliced pgRNA variants during HBV infection was partly genotype-related. 14,[27][28][29] It would be interesting to determine whether serum HBV RNA was spliced differently from intrahepatic HBV RNA in the same individual; (4) subgenomic HBV RNA: circulating hepatitis B virus X protein (HBx) RNA was also observed in CHB patients, 14,18,30 but the subgenomic HBV RNA such as HBx RNA, if any, only represent the minority of total extracellular HBV RNA 10,14,18 ; (5) HBV-human chimeric RNA: recently, the presence of HBV-human chimeric RNA was reported in serum samples of CHB patients from integrated HBV DNA, including 5'-HBV-human-3' and 5'-human-HBV-3' transcripts accounting for a minimal proportion of serum HBV RNA. 10,31 Previous studies found that some HBV-human chimeric RNA could be detected in HBV-associated HCC tumour tissues which can promote hepatocarcinogenesis by functioning as a long noncoding RNA and depleting cellular miR-122.…”
Section: Species Of Extracellular/serum Hbv Rnamentioning
confidence: 99%
“…This overlapping nature of HBV mRNAs, together with the high diversity of other non-canonical mRNAs produced during HBV infection, has been a bottleneck to studying the expression profiles of different HBV mRNA expressed during infection. In this context, long-read RNA sequencing has emerged as a promising tool for the characterization of the HBV transcriptome [ 46 , 47 ].…”
Section: Viral Gene Expression From the Hbv Minichromosomementioning
confidence: 99%